Resilience of farmer families affected by the Cianjur Earthquake: The impact vulnerability, economic stress, and coping strategies - Sunarti Euis; Kumalasari Berti; Yuliarti Siroj Eko (BIO Web of Conferences)
The Cianjur Earthquake in November 2022 had a profound and lasting impact on the lives of the families affected. The objective of this research is to: (1) analyze the resilience of farmer families who survived the earthquake in relation to vulnerability, economic pressure, and coping strategies carried out by families, and (2) analyze the differences in the variables studied in two family groups (severely and lightly damaged houses). The study was conducted one year after the disaster, involving 162 farming families (81 families each with heavily and lightly damaged houses). All research variables had adequate reliability (α>0.7). Compared to those with lightly damaged houses, farming families with severely damaged houses had lower resilience and coping strategies, but higher subjective vulnerability and economic stress. The SEM-PLS test results show that vulnerability has a significant effect on family resilience, while coping strategies have an effect at a significant level of 8%. Family vulnerability also has a significant effect on subjective economic pressure and coping strategies. Vulnerability, economic pressure, and coping strategies contributed 31.2 percent to family resilience. These results show the central role of family vulnerability, so it is important to make efforts to mitigate and reduce disaster risk through reducing family vulnerability in disaster-prone areas. This study demonstrates that family resilience serves as a crucial factor in the effective incorporation of disaster risk reduction within the Sustainable